Water as a tuneable solvent: a perspective. (2nd April 2020) - Breynaert, Eric; Houlleberghs, Maarten; Radhakrishnan, Sambhu; Grübel, Gerhard; Taulelle, Francis; Martens, Johan A.
Abstract : Water is the most sustainable solvent, but its polarity limits the solubility of non-polar solutes. Confining water in hydrophobic nanopores could be a way to modulate water solvent properties and enable using water as tuneable solvent (WaTuSo). Abstract : Water is the sustainable solvent of excellence, but its high polarity limits the solubility of non-polar compounds. Confinement of water in hydrophobic pores alters its hydrogen bonding structure and related properties such as dielectric constant and solvation power. Whether this special state of confined water can be rendered useful in chemical processes is hitherto underexplored. Confining water in hydrophobic nanopores could be a way to modulate water solvent properties, enabling the use of water as a tuneable solvent (WaTuSo). Applying pressure forces a heterogeneous mixture of poorly soluble molecules and water into hydrophobic nanopores of a host material where the lowered polarity of water enhances dissolution. Decompression after reaction causes expulsion of the solution from the pores and spontaneous demixing of reaction products because water returns to its normal polar state. Temporary dissolution enhancement during confinement is expected to be advantageous to chemical reaction and molecular storage. Nano-confined water offers a potential alternative to compression for storing CH4 and H2 gas, and opens new opportunities for green chemistry such as aqueous phase hydrogenation reactions which benefit from enhanced hydrogen solubility. Unprecedented control in time and space over H2 O solvation properties in a WaTuSo system will enable new technologies with major scientific and societal impact.